A review of incorporating Nd:YAG laser cleaning principal in automotive industry. Issue 4 (October 2018) - Razab, Mohammad Khairul Azhar Abdul; Mohamed Noor, An'amt; Suhaimi Jaafar, Mohamad; Abdullah, Nor Hakimin; Suhaimi, Fatanah Mohamad; Mohamed, Mazlan; Adam, Noraina; Auli Nik Yusuf, Nik Alnur
Abstract: Laser cleaning has been identified as an ideal technology to replace conventional chemical techniques in the motorcar coating removal process to maintain the sustainability of our environment. This is due to the unique characteristics of this cleaning technique, such as being versatile, precise, controllable, lack of waste generation, and environmental friendly process. This laser technique can remove the coating layers without using chemical products and prevents the metal substrate surfaces from defect. This paper reviews the potential of incorporating pulsed Nd:YAG laser and its principals in coating removal for automotive industry with respect to these characteristics.